Educação católica, gênero e identidades: O Colégio Santa Rita de Areia na História da Educação Paraibana (1937-1970). - Correia, Maria Ivete Martins (2010)
Considering the omnipresence of women in education, specially in the catholic girls schools, and its almost invisibility in official registers of Paraíba s Education History, this study has as objective to understand the game of relations established in the project of catholic education developed for the Franciscan of Dillingen nuns in the Colégio Santa Rita (catholic high school), in the city of Areia, from 1937 to 1970, and its implications in the constitution of genre and professional identities of the girls who studied there. The research is based upon Michel Foucault ideas as theoretical references, articulating the categories catholic education, genre and identity, choose to guide this study. The work was developed from the applied genealogical inquiry to the analysis of the bibliographical and documental sources (documents of the Catholic Church, the Franciscan order and Colégio Santa Rita; memories and memorabilia of former-pupils; Franciscans nuns and former-pupils interviews, and also local newspapers). In that way, in six chapters the text treats on the Catholic Ultramontane thought, the Order of the German Franciscans Sisters of Dillingen, the city of Areia (Paraíba State, Northeast Brazil), the German pioneers nuns, and the Colégio Santa Rita in its architectural arrangement, its pedagogical and disciplinary aspects, by the concept of panopticism. The text also analyzes the memories of six former-pupils from that educational institution, from the Foucault s concepts of technologies of the self and governmentality. The thesis of this work is that the Education developed in the Colégio Santa Rita, based upon the Catholic canon, was an important aspect in Paraíba s educational context from 20th century 30 s to 70 s and had a main role in the ordering of local society and also in the process of identity constitution of girls who studied submitted to that pedagogical model.